(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The text problematizes the distinction between gender performance and gender performativity through an artistic performance by Pêdra Costa and several texts of performance studies. The author argues that, instead of opposing performance and performativity, it is necessary to emphasize what exists between these two dimensions that are inseparable, especially in both feminist and or in sexual and gender dissent arts.